Business continuity solution with Red Hat OpenShift and IBM Spectrum Virtualize for Public Cloud on Microsoft Azure. (IBM Redbooks, 2022)
The focus of this Blueprint is to facilitate the deployment of the hybrid cloud business continuity solution with Red Hat OpenShift Container Platform (RHOCP) on Microsoft Azure Cloud and Container Storage Interface (CSI) driver plug-in for IBM Block Storage and IBM® Spectrum Virtualize for Public Cloud (SV4PC) on Microsoft Azure Cloud. This solution is designed to protect the data by using IBM Storage-based Global Mirror Replication, and the "volume replication" feature from IBM block storage CSI driver for IBM Storage. For demonstration purposes, MySQL containerized database is installed on the persistent volume (PV) that is created on the on-premises IBM FlashSystem® Storage. This storage is connected to the RHOCP cluster in the vSphere environment. CSI driver plug-in for IBM Block Storage (FS9100) and SV4PC on Azure is installed on Red Hat OCP on Azure and On-premises Red Hat OCP. The volume or logical unit number (LUN) from on-premises IBM FlashSystem Storage (FS9100) is replicated to IBM SV4PC on Microsoft Azure Cloud by using the IBM storage global mirror replication feature and the IBM CSI volume replication feature.